Cd exposure-triggered metabolic disruption increases the susceptibility of Lymantria dispar (Lepidoptera: Erebidae) larvae to Mamestra brassicae nuclear polyhedrosis virus: A multi-omics study - Dun Jiang; Mingtao Tan; Lin Zheng; Hongfei Wu; Yaning Li; Shanchun Yan (Ecotoxicology and Environmental Safety, 2022)
Biological control is an environmentally friendly and effective pest control strategy, but it is often affected by a variety of abiotic factors in the pest control area. Here, the susceptibility of gypsy moth larvae to Mamestra brassicae nuclear polyhedrosis virus (MbNPV) under Cd treatment at the low and high dosages was investigated, and the mechanism of Cd stress affecting virus susceptibility of gypsy moth larvae was analyzed from a metabolic perspective by combining transcriptome and metabolome of the larval fat body. Our results showed that the mortality of MBNPV infection on gypsy moth larvae pre-exposed to Cd was significantly higher than that of larvae without Cd pre-exposure, and the joint effects of Cd exposure and virus infection on larval mortality were demonstrated to be synergistic. Transcriptome analysis revealed that amino acid and carbohydrate transport and metabolism accounted for most of the differently expressed genes in the low Cd and high Cd treatment groups. Consistent with the transcriptome results, metabolome analysis also showed that most metabolites affected by Cd exposure were involved in amino acid and carbohydrate metabolism. Function analysis showed that the contents of several amino acids (e.g. tryptophan and tyrosine) with antioxidant properties were significantly increased in Cd-treated gypsy moth larvae. Taken together, Cd exposure as an environmental factor, promotes the susceptibility of gypsy moth larvae to MbNPV, and metabolic disruption, especially amino acids and carbohydrates-related metabolism, is responsible for the increased susceptibility of gypsy moth larvae to virus under Cd stress.